2019
DOI: 10.1002/ijc.32407
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐mapping of a novel premenopausal breast cancer susceptibility locus at Chr4q31.22 in Caucasian women and validation in African and Chinese women

Abstract: We previously identified a novel breast cancer susceptibility variant on chromosome 4q31.22 locus (rs1429142) conferring risk among women of European ancestry. Here, we report replication of findings, validation of the variant in diverse populations and fine‐mapping of the associated locus in Caucasian population. The SNP rs1429142 (C/T, minor allele frequency 18%) showed association for the overall breast cancer risk in Stages 1–4 (n = 4,331 cases/4271 controls; p = 4.35 × 10−8; odds ratio, ORC‐allele,1.25), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…With the development of high‐throughput technology, emerging evidence demonstrated that genetic alterations, including single‐nucleotide polymorphisms (SNPs), insertions, deletions, and copy number variations, were associated with the risk of various diseases including BC . Notably, SNPs, especially in irregular regions of protein‐coding and related with diseases, have been extensively studied and reported widely .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of high‐throughput technology, emerging evidence demonstrated that genetic alterations, including single‐nucleotide polymorphisms (SNPs), insertions, deletions, and copy number variations, were associated with the risk of various diseases including BC . Notably, SNPs, especially in irregular regions of protein‐coding and related with diseases, have been extensively studied and reported widely .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-throughput technology, emerging evidence demonstrated that genetic alterations, including single-nucleotide polymorphisms (SNPs), insertions, deletions, and copy number variations, were associated with the risk of various diseases including BC. 5,6 Notably, SNPs, especially in irregular regions of protein-coding and related with diseases, have been extensively studied and reported widely. 7 The expression of the same lncRNA transcripts varies by different health conditions, age, tissues, even cells, which can indicate their potential as possible biomarkers and be predictive of diagnosis and prognosis of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…With the awareness of genetic counseling, single nucleotide polymorphisms (SNPs) are extensively used to evaluate the susceptibility to cancer. [4][5][6] However, it still needs a great effort to find more SNPs to draw the genetic map of lung cancer.…”
Section: Introductionmentioning
confidence: 99%